Misleading Translation of What is Philosophy? by Gilles Deleuze and Félix Guattari - Žukauskaitė, Audronė (Problemos, 2022)
Deleuze, G., Guattari, F., 2019. Kas yra filosofija? Vertė Daina Habdankaitė, Nijolė Keršytė. Vilnius: Jonas ir Jokūbas, 242 p. ISBN 978-609-8236-06-4
Keywords: -